Transaction Cost Analysis on The Financing of The Baitul Maal Wat Tamwil - Setyowati, Ro'fah; Darwanto, Darwanto; Adityawarman, Adityawarman; Notolegowo, Hantoro Ksaid (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
The emergence of Sharia microfinance institutions (S-MFIs) BMT has become a hope for micro, small and medium enterprises (MSMEs) pertaining to the improvement of access to capital loans, business, and welfare of MSME entrepreneurs. This study delves deeper into ex-ante and ex-post transaction costs of the BMT financing scheme at MSMEs from the BMT side and formulates strategies for optimizing BMT financing schemes for MSMEs. Constituting the largest contributor to the overall transaction costs at MSMEs, In a bid to reinforce the financing process, the efficiency of ex-ante transaction costs for drafting and ex-post transaction costs for designing and implementing the BMT’s governance is required.